2018
DOI: 10.1016/j.jebdp.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Effectiveness of Rotary Nickel-Titanium vs Manual Stainless Steel Instruments for Root Canal Therapy: Systematic Review and Meta-analysis

Abstract: The results of this systematic review suggested that NiTi rotary instruments were associated with lower canal transportation and apical extrusion when compared to SST hand files, whereas both groups had similar outcomes in terms of success of therapy, amount of residual bacteria, and cleansing ability after treatment. However, due to the limited evidence available, these results should be interpreted with caution. Consequently, more randomized control trials using standardized protocols are needed in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 81 publications
2
47
1
8
Order By: Relevance
“…Which concept for root canal treatment is the best? A recent review article reported that the heterogeneity and the limited number of clinical studies, as well as their insufficient case numbers for the purpose of meta-analyses prevent drawing reliable conclusions (Del Fabbro et al, 2018). The results of the present study show a statistically significant higher tooth survival rate without untoward events for endodontic treatments using reciprocating root canal instrumentation supplemented with PUI compared to hand instrumentation with syringe irrigation.…”
Section: Discussioncontrasting
confidence: 47%
“…Which concept for root canal treatment is the best? A recent review article reported that the heterogeneity and the limited number of clinical studies, as well as their insufficient case numbers for the purpose of meta-analyses prevent drawing reliable conclusions (Del Fabbro et al, 2018). The results of the present study show a statistically significant higher tooth survival rate without untoward events for endodontic treatments using reciprocating root canal instrumentation supplemented with PUI compared to hand instrumentation with syringe irrigation.…”
Section: Discussioncontrasting
confidence: 47%
“…Using of NiTi-RIs during endodontic postgraduate programmes’ training is a routine policy. In addition, endodontists are well aware of the advantages of using NiTi-RIs over SSIs such as: greater resistance to failure [ 4 ], greater centring ability [ 19 , 20 ], less instrumentation time [ 21 ], less complications [ 9 ] and may lead to better outcomes [ 6 , 22 ]. By contrast, the proportion of GDs who were using NiTi-RIs (60%) was significantly less than that of endodontists.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The invention of the NiTi rotary instrumentation was advantageous in minimizing the procedural errors and time of treatment. 6 A new technique for instrumentation was introduced by Yared, where a single file was used in a reciprocating motion rather than rotation, overcoming the large sequence of files used in a rotation motion. 7 Although some studies described the higher performance of the reciprocating Eur J Dent 2020;14:70-76 motion, other studies showed that the rotary files produced more centralized preparations and less transportation.…”
Section: Introductionmentioning
confidence: 99%